Pemanfaatan Perpustakaan Sebagai Pusat Sumber Belajar Bagi Masyarakat di Kantor Arsip Perpustakaan dan Dokumentasi Kota Padang - Aufa, Fadhilla; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purposes of this study were to the use of the library as a learning resource center for the community in the Kantor Arsip Perpustakaan dan Dokumentasi Kota Padang and what obstacles faced by people in the use of the library as a learning resource center. Data were collected through observation and interviews in the Kantor Arsip Perpustakaan dan Dokumentasi Kota Padang. The data were analyzed descriptively. Based on the results of the study be concluded the following: (1) the public use the library in the Kantor Arsip Perpustakaan dan Dokumentasi Kota Padang to add information in the learning activity, provide a reference or references to obtain learning materials, (2) the constraints in using the library, the lack of promotion of the library to the community, facilities and infrastructure that are less complete, less participating librarians, and collection is still not complete, (3) the business to be done by the use of the library in the library, the more optimal promotion, facilities and infrastructure that is equipped , as well as the training of librarians and collection more complete. Therefore it is advised, (1) the procurement of the library collection should pay attention to where the collection is much needed visitors as a source of learning, (2) the library should be to provide funds for the procurement of library collections and promotes both through mass media and electronic media so that the public know of the existence library; (3) librarians should be actively serving visitors to find the information needed. Keywords: learning resources; utilization library